Mathematical Modelling of molecular adsorption in zeolite coated frequency domain sensors. Issue 1 (2015) - Murrieta-Rico, Fabian N.; Mercorelli, Paolo; Sergiyenko, Oleg Yu.; Petranovskii, Vitalii; Hernández-Balbuena, Daniel; Tyrsa, Vera
Abstract: Fast and accurate information is important for most monitoring, data acquisition, and monitoring systems; sensors are transducers that allow to accomplish such task. In this work different kinds of resonant sensors known as frequency domain sensors are reviewed; also frequency measurement techniques are explored; finally resolution improvement is proposed and analyzed for using frequency domain sensors by mathematical modelling.